Cloud usability features to support knowledge transformation in design learning - Mohamad, Nur Aziemah (2019)
Critique is one of the essential phases in Architectural design learning and lecturers often provide feedback to students regarding their proposed artefact in a studio environment. It contains tacit knowledge because of the interactions that occur between lecturers, students and the artefact. The current tools that are available and used by students such as AutoCAD, Revit and similar ones are mostly static and have limitations in capturing the interaction between the agents. The process of knowledge transformation between tacit and explicit needs to be represented in order to create a more rigorous feedback from the lecturer to improve the student’s artefact. Hence, the aim of this study is to develop a knowledge transformation model for a design learning critique session starting from tacit to explicit knowledge supported by cloud usability feature which is explode. To organise this research, a design science approach was used as the methodology that relied on qualitative data for analysis. A recorded observation during the Architecture design subject was conducted to view the types of feedback that occurred during the critique session. Feedback through the dialogues underwent an initialisation process using thematic analysis. From the process, the extracted data were categorised based on an established feedback typology model, which are meaning-level feedback and error correction. Based on the observation, a knowledge transformation model using cloud usability features was developed for this research and validated by three experts from the knowledge management discipline using questionnaire. The validation encompasses three components, namely knowledge management in design learning, feedback as knowledge transformation process and use of cloud usability features to support it. All the experts agreed that cloud usability features can support the knowledge transformation in design learning. Once validated, the model was implemented in a simulated critique session of a studio class to get the Architecture participants’ feedback on the knowledge representation. Another set of questionnaire comprising the same components as given to the experts were given to them. The findings showed that they agreed the use of cloud usability feature supports the knowledge transformation in design learning. Thus, based on the findings, it shows that the feedback can become more rigorous when knowledge is transformed explicitly with the assistance of a tool.